The Implementation of Fiqih Learning Based on Science Integration through Online Learning of Covid-19 in School - Nurjannah, Salma; Sinaga, Ali Imran; Hafsah, Hafsah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to describe the implementation of learning fiqh based on the integration of knowledge online during the Covid-19 period in schools. The type of this research is qualitative with a descriptive study method. In this context, researchers need to observe all the facts that occur in the field (research background) with data collection techniques in the form of in-depth interviews, participant observation, and efforts to correlate (crosscheck) data with document studies. Data analysis uses reduction techniques, data presentation, and verification. The results of this study indicate that the implementation of fiqh learning as a sub-subject of Islamic Religious Education (PAI) based on knowledge integration has been carried out effectively through the online system during the Covid-19 period. This is marked by (1) the ability of PAI teachers to design good online learning tools, as evidenced by learning tools according to the Ministry of Education and Culture during the Covid-19 period; (2) the ability of PAI teachers to carry out the online learning process well, as evidenced by supporting applications such as WhatsApp, zoom, google classroom, google form; and (3) the learning process is carried out in accordance with the learning tools made. The supporting factors for this implementation are the creativity of teachers and students in the online learning process, while the obstacles are students' indiscipline, lack of focus on learning. For this reason, an alternative solution for more effective online learning is through structured and periodic training provided to teachers.